Paleoclimate of the Nepal Himalayas during the Last Glacial: Reconstructing from glacial equilibrium-line altitude - Asahi, Katshuhiko; Watanabe, Teiji (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp. 100-1